Comparative analysis of pedagogical and professional competencies of elementary school teachers in Indonesia and Finland - Neng Ana Aprilya Nupus; Annisa Nurhayati; Mutia Rahmalia; Sholeh Hidayat; A'i Wahyuni (Privietlab, 2026)
This article presents a comparative literature review examining pedagogical and professional competence among elementary school teachers in Indonesia and Finland, with the aim of generating policy-relevant insights for teacher development in Indonesia. Existing studies on teacher competence often emphasize isolated components, such as certification, curriculum compliance, or professional development, without sufficiently addressing how these elements interact within broader education systems. Drawing on recent international literature published between 2023 and 2025, this review adopts a multidimensional analytical framework that encompasses pedagogical practice, professional preparation, institutional support, and systemic coherence. The findings indicate that teacher competence is not solely determined by individual capability or formal qualifications but by the alignment between teacher education, professional autonomy, assessment practices, and ongoing professional learning structures. Finland has a coherent competence ecosystem characterized by research-based teacher education, strong professional trust, and reflective pedagogical practice. Although Indonesia is supported by national standards and certification systems, it continues to face challenges related to implementation consistency, administrative burden, and uneven professional learning opportunities. This article argues that strengthening teacher competence requires systemic integration rather than incremental reform and offers strategic directions for enhancing elementary teacher professionalism in Indonesia.